2020
DOI: 10.1111/ppa.13142
|View full text |Cite
|
Sign up to set email alerts
|

A broad diversity survey of Rhizoctonia species from the Brazilian Amazon reveals the prevalence of R. solani AG‐1 IA on signal grass and the new record of AG‐1 IF on cowpea and soybeans

Abstract: Leaf blight, sheath blight, and web blight are major diseases caused by Rhizoctonia species on both Fabaceae and Poaceae plant hosts in the Brazilian Amazon agroecosystem. To determine the diversity of Rhizoctonia species associated with foliar diseases on fabaceous (cowpea and soybean) and poaceous (rice and signal grass [Urochloa brizantha]) hosts, a broad survey was conducted in Pará, Rondônia, Roraima, and Mato Grosso, in the Amazon, from 2012 to 2013. We extended our survey to Cerrado areas of Mato Grosso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 31 publications
(72 reference statements)
0
12
0
Order By: Relevance
“…The experimental design employed was completely randomized blocks with eight treatments and four replicates and one repetition of the entire experiment in time. The mean disease severity for the groups of isolates followed by the same letter (figure 7) is not significantly different according to a contrast of means at p ≤ 0.05 (Chavarro-Mesa et al, 2015, 2020Ramos-Molina et al, 2016). The rating of the experimental unit involved the combined scores from the four plants.…”
Section: Cross Pathogenicity Testmentioning
confidence: 97%
“…The experimental design employed was completely randomized blocks with eight treatments and four replicates and one repetition of the entire experiment in time. The mean disease severity for the groups of isolates followed by the same letter (figure 7) is not significantly different according to a contrast of means at p ≤ 0.05 (Chavarro-Mesa et al, 2015, 2020Ramos-Molina et al, 2016). The rating of the experimental unit involved the combined scores from the four plants.…”
Section: Cross Pathogenicity Testmentioning
confidence: 97%
“…In Latin America, Africa, and Asia, sheath blight (SB) and banded leaf and sheath blight (BLSB) caused by R. solani AG-1 IA are considered widespread diseases of rice and maize Zhao et al 2006). It had been reported that various AGs of R. solani infested other crops and ornamental plants such as cabbage (Türkkan et al 2020), pepper (Tuncer and Eken 2013), chrysanthemum (Bueno et al 2013), legume (pulse crops) (Dubey et al 2012), medicinal herbs (de Melo et al 2018), tobacco (Cárdenas et al 2015), and signal grass (Chavarro-Mesa et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Web blight is endemic in Central America and the Caribbean (Godoy‐Lutz et al., 2008; Rodríguez et al., 1999b; Rajnauth, 1987), the Brazilian Amazon agroecosystem (Alves de Souza et al., 2014; de Jesus Boari et al., 2020; Chavarro‐Mesa et al., 2020), northwestern Argentina (Spedaletti et al., 2016), Ecuador (Villamar‐Torres et al., 2018), and Africa (Masangano & Miles, 2004; Wortmann et al., 1998). Upmanyu and Gupta (2005) reported that WB is a serious disease of snap bean ( P. vulgaris L. var.…”
Section: Introductionmentioning
confidence: 99%
“…Crop Science (Alves de Souza et al, 2014;de Jesus Boari et al, 2020;Chavarro-Mesa et al, 2020), northwestern Argentina (Spedaletti et al, 2016), Ecuador (Villamar-Torres et al, 2018), and Africa (Masangano & Miles, 2004;Wortmann et al, 1998). Upmanyu and Gupta (2005) reported that WB is a serious disease of snap bean (P. vulgaris L. var.…”
Section: Introductionmentioning
confidence: 99%